A high-quality factor dielectric resonator antenna for use in a wireless high-temperature sensor. Issue 1 (24th January 2020) - Li, Chih-Hung; Chen, Yih-Chien; Lin, Tse-Lung; Kuoa, Cheng-Chien
Abstract: The microwave dielectric properties of (Mg0.93 Ni0.07 )2 SnO4 ceramics were examined with a view to their exploitation for wireless high-temperature dielectric resonator antenna temperature sensor. A dielectric constant of 8.1, a quality factor of 124, 200 GHz, and a temperature coefficient of the resonant frequency of −67 ppm/°C were obtained for (Mg0.93 Ni0.07 )2 SnO4 ceramics that were sintered at 1550 °C for 4 h. The developing procedures and test results for dielectric resonator antenna temperature sensor were recorded. The resonating frequency and 3 dB bandwidth measured at 25 °C were 12.62 GHz and 53 MHz, respectively. A sensitivity of −0.99 MHz/°C was successfully achieved.